A clinical evaluation on the alkalization of local anesthetic solution in periapical surgery - Fa'iz A Al-Sultan; Wafaa Kh Fathie; Rayan S Hamid (University of Mosul, College of Dentistry, 2006)
Abstract Aims: To assess the effect of alkalization of local anesthetic solution for the purpose of enhancing its efficiency in periapical surgery. Materials and Methods: A total sample of 80 patients, all needing periapical surgery on one or more of their upper anterior tooth (teeth) was subjected to this trial. For the purpose of comparison, the sample was randomly divided into two groups based on the local anesthetic solution that they were to receive before surgery. The first group(control) included those patients who received the commercially available local anesthetic solution with a standard pH of 3.5.The second group (trial group) included those patients who received a pH adjusted local anesthetic solution at 7.2 (using sodium bicarbonate).Prior to, and at the completion of intended surgery, the following data were recorded: Pain during injection, onset of achievement of surgical anesthesia, pain during operation and the duration of operation itself. Results: A significant difference in regard to onset of achievement of surgical anesthesia between both groups was noticed with a faster onset in group two where the patients received a pH adjusted local anesthetic solution when compared to control group where the patients received the commercially available local anesthetic solution. Also, less pain on deposition of solution was noticed in the second group as well as less pain score levels were recorded during operation in regard to the same group. Conclusion: The pH adjusted local anesthetic solutions may provide certain advantages when compared to the commercially available local anesthetic solutions regarding enhancement of anesthetic efficiency, reduced pain on injection as well as during surgery